Frontières et circulations au Moyen-Orient (Machrek/Turquie) - Véronique Bontemps; Philippe Bourmaud; Cyril Roussel (L'Espace Politique)
Introductory article of the issue 27 (2015-3) of the journal L’Espace politique entitled "Borders and Circulations in the Middle East (Machrek / Turkey)"